2013
DOI: 10.1155/2013/126870
|View full text |Cite
|
Sign up to set email alerts
|

Cracks Detection Using Active Modal Damping and Piezoelectric Components

Abstract: Abstract. The dynamics of a system and its safety can be considerably affected by the presence of cracks. Health monitoring strategies attract so a great deal of interest from industry. Cracks detection methods based on modal parameters variation are particularly efficient in the case of large cracks but are difficult to implement in the case of small cracks due to measurement difficulties in the case of small parameters variation. Therefore the present study proposes a new method to detect small cracks based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While in an actual NDT system the measurement data is obtained via an experiment in an actual NDT system, e.g. by using piezoelectric sensors (Michaels and Michaels 2003) or a scanning laser vibrometer (Ishak et al 2002) etc., the measurement data can be also generated via simulations (Chomette et al 2013). Mathematically, two types of approaches are related to NDT via numerical wave excitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in an actual NDT system the measurement data is obtained via an experiment in an actual NDT system, e.g. by using piezoelectric sensors (Michaels and Michaels 2003) or a scanning laser vibrometer (Ishak et al 2002) etc., the measurement data can be also generated via simulations (Chomette et al 2013). Mathematically, two types of approaches are related to NDT via numerical wave excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of a system and its safety can be considerably affected by the presence of cracks. Crack detection methods based on dynamic load parameters are particularly efficient (Chomette et al 2013). The NDT method uses the measured amplitudes of a scattered single-frequency signal to identify the crack.…”
Section: Introductionmentioning
confidence: 99%
“…Han [18] and Patel and Darpe [19] showed that the method based on fracture mechanics, using stress intensity factors and the energy release rate to calculate the stiffness, combined with a breathing function, can increase the efficiency of the dynamic analysis. Bifurcation diagram, orbit plot, and Poincare map were employed to investigate the numerical simulation of transient response of the cracked rotor system to find the nonlinear dynamic characteristic of the cracked rotor [20][21][22][23][24] based on the two basic model of open-close cracked rotor, both switching and breathing models. These studies exhibited the splendid visualized comparisons and provide the nonlinear signals directly for monitoring and diagnosing fault of rotating machines.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the recognition of this influence is very important due to its great values of practical application. There are a number of theoretical crack-modeling techniques in the literature, which can be basically grouped into two categories: lumped flexibility models [10][11][12][13][14][15] and continuous stiffness models [16][17][18][19][20][21][22]. For the lumped flexibility models, a crack is represented by a rotational spring.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the energy distribution near the cracktips, Swamidas et al [20] established continuous bending and shearing stiffness models for the cracked beams. Chomette et al [21], by means of the continuous beam models, proposed a new method to detect the small cracks in beam structures.…”
Section: Introductionmentioning
confidence: 99%